(untitled) (American & British Studies Annual, 2015)
The following article deals with the work of distinguished British conservative journalist and public intellectual Peter Oborne (b. 1957). In his published oeuvre, Oborne has been particularly concerned with the political culture during the administration of Anthony Charles Lynton Blair (1997-2007). This article analyses Oborne’s books and focuses on his major themes: his koncept of the British “Political Class” as well as the deterioration of standard British institutions, the rise of the media, the widespread mendacity of British politicians and, finally, the triumph of “post-democratic” values characterized by a slow demise of the British electorate in relation to the political process. The article discusses wider contexts of contemporary British conservatism and assesses Oborne’s contribution to the debate about the perspectives of British political identity and its cultural and democratic traditions.